Effectiveness of Oxytocin Massage on Anxiety Scales Among Primiparous Postpartum Mothers: Efektivitas Pijat Oksitosin terhadap Skala Kecemasan pada Ibu Nifas Primipara - Mardelia Astriani; Olivia Tri Monica; Bella Rachmasari (Poltekkes Kemenkes Palu, 2026)
Background: Anxiety is a common psychological concern during the postpartum period, particularly among primiparous mothers who are adapting to maternal roles for the first time. Non-pharmacological interventions that are simple, accessible, and applicable in routine postpartum care are therefore needed. Oxytocin massage may promote relaxation and potentially reduce maternal anxiety. This study aimed to determine the effectiveness of oxytocin massage in reducing anxiety among primiparous postpartum mothers. Methods: This study used a quasi-experimental pre-test and post-test control group design involving 30 primiparous postpartum mothers. Participants were allocated into an intervention group receiving oxytocin massage (n = 15) and a control group receiving standard care (n = 15). Anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HARS). Within-group changes were analyzed using paired-samples t-tests, while differences in anxiety score reduction between groups were assessed using an independent-samples t-test. Results: The mean HARS score in the intervention group decreased from 24.73 before the intervention to 14.27 after the intervention, representing a mean reduction of 10.20 points. In the control group, the mean HARS score decreased slightly from 23.93 to 23.27, with a mean reduction of 0.67 points. The reduction in anxiety scores was significantly greater in the intervention group than in the control group (t = 19.207; p < 0.001). Conclusion: Oxytocin massage was associated with a significantly greater reduction in anxiety among primiparous postpartum mothers compared with standard care. These findings indicate that oxytocin massage may be considered a simple non-pharmacological supportive intervention for anxiety management during early postpartum care